Pengetahuan dan Sikap Masyarakat dalam Upaya Pencegahan Penyakit Tuberkulosis Paru: Tinjauan Pustaka - Mulu, Servasius To'o Jala (Poltekkes Kemenkes Kupang, 2021)
Background: Pulmonary Tuberculosis is a leading cause of death in many countries around the world. The lack of information available to the public can affect their knowledge and efforts in preventing the transmission of Pulmonary Tuberculosis. If this issue is left unaddressed, it could lead to widespread transmission of Pulmonary Tuberculosis, with an increasing incidence and a rising death toll. Objective: To assess the public's knowledge and attitudes toward preventing Pulmonary Tuberculosis. Methods: This study uses a literature review method, consisting of problem identification, data collection through the Google Scholar database using the keyword “Public Knowledge and Attitudes in Preventing Pulmonary Tuberculosis.” Screening was then carried out according to the criteria, including journal articles published in the last five years, original article types, full-text access, and national journal articles. The next steps involved summarizing and analyzing the data using PICO, with the process illustrated in a PRISMA chart. Results: The literature review, based on 10 journal articles, found that seven journals reported good knowledge, while three journals indicated sufficient knowledge regarding the prevention of Pulmonary Tuberculosis. Additionally, eight journal articles showed positive or good attitudes, and one journal article indicated a sufficient attitude towards efforts in preventing Pulmonary Tuberculosis.